Effect of flame spray deposition parameters on the microstructure, microhardness and corrosion resistance of FeNbC coatings on AISI 1020 steel. (8th May 2019) - Bonetti, I; dos S de, E A; da Costa, C E; Paredes, R S C; Sucharski, G B; da Costa, E M; Franco, E; Milan, J C G
Abstract: The present study aimed to produce and characterize FeNbC coatings deposited on AISI 1020 steel using flame spray process (FS) evaluating the influence of powder granulometry, standoff distance, powder feed rate and substrate preheating. FS process parameters variations produce coatings with different properties. Taguchi experimental design based in the L9 orthogonal array and ANOVA statistical analysis were performed. Coating morphology was evaluated using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS), the present phases were identified by x-ray diffraction (XRD). Coatings microhardness was evaluated using Knoop hardness test. The coatings corrosion resistance was measured through monitoring the open circuit potential and potenciodynamic polarization in 3.5% NaCl solution. The results indicate that coatings with microhardness average of 1084 HK0.3 and dispersion of the measured values were associated with heterogeneity and interlamellar oxides formed in the microstructure. All control factors investigated showed significant influence on microhardness. Substrate preheating was the most important factor, followed by the powder granulometry; powder feed rate and standoff distance. The FeNbC coating presented a reduction in the substrate corrosion rate, but the presence of defects in the microstructure, such as porosities, voids and cracks compromised the barrier effects of these coatings.